2022
DOI: 10.1128/spectrum.02438-22
|View full text |Cite
|
Sign up to set email alerts
|

Hexyl-Aminolevulinate Ethosomes: a Novel Antibiofilm Agent Targeting Zinc Homeostasis in Candida albicans

Abstract: Candida albicans is the most prevalent fungal species of the human microbiota. The medical impact of C. albicans on its human host depends on its ability to form biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…C. albicans strain SC5314 was obtained from our research group [ 6 , 7 ]. C. albicans was cultivated on YPD plates at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…C. albicans strain SC5314 was obtained from our research group [ 6 , 7 ]. C. albicans was cultivated on YPD plates at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…After sufficient incubation time, the suspension was centrifuged and washed twice with sterile PBS to remove the drug solution, and the cells were resuspended with RPMI 1640 medium and immediately irradiated for 30 min using a light-emitting diode (LED) light source (Wuhan Yage Photonics Co., Ltd., Wuhan, China). Using the serial dilution method, in each group of the suspension, we performed gradient dilution [ 7 ], and ultimately, 10 μL of serially diluted cell suspension was coated on the YPD agar plate, subjected to 37 °C incubation for 24 h for colony counting, and we performed three independent experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…55 Multidrug ethosomes are a promising area of research in drug delivery systems for hair loss treatments. Wang et al (2022) 56 demonstrated the potential benefits of combining two or more drugs in a single vesicular formulation. By targeting multiple mechanisms of hair loss, multidrug ethosomes could improve the efficacy of hair loss treatments.…”
Section: Ethosomes For Hair Lossmentioning
confidence: 99%